New masters of poster design : poster design for the next century - Foster, John, 1971-; Rockport Publishers (Gloucester, Mass. : Rockport, 2008)
From the Publisher: In much the way that the CD replaced the album, the poster has waned as a messaging vehicle. The poster has now become a postcard and e-mail blast, leaving many to long for the lost age when posters were not only major promotional vehicles, but also artwork worthy of framing. Some of the world's best designers just could not stand idle while the poster fell by the wayside. They turned to the poster for personal expression and as an outlet from more restrictive mediums. This book showcases their breathtaking artwork, which has proven that the poster can still serve as a worthy communications tool. In doing so, they've brought the poster back to prominence. In this book, the author has compiled the world's finest new work at the height of this rebirth. There is currently no book on the market that can claim it features a "definitive" poster collection.
-- Introduction -- Aesthetic apparatus -- François Caspar -- Fang Chen -- Cyan -- Oded Ezer -- Hakobo (Jakub Stepien) -- Hammerpress -- Hedram Harby -- Jiamping He -- Hendersonbromsteadartco -- Fons Hickmann (M23) -- Jewboy Corporation -- Andrew Lewis Design -- Little Friends of Printmaking -- Luba Lukova -- Methane Studios -- Modern Dog -- Patent Pending Design -- Sandstrom Design -- Seripop -- Spotco -- Spur Design (Dave Pluckert) -- Slavimir Stojanovic (Futro) -- Studio Boot -- Yuri Surkov -- Sussner Design Company -- The Heads of State -- Thinkmule -- Thirst (Rick Valicenti) -- Martin Woodtli -- The Next Wave -- Afterword.
Originally published: 2006.
Keywords: Posters -- 21st century -- Catalogs